2012
DOI: 10.1088/1748-0221/7/05/p05002
|View full text |Cite
|
Sign up to set email alerts
|

Charge collection measurements on slim-edge microstrip detectors

Abstract: We have generated slim edges on manufactured silicon strip detectors by cleaving the non-active edge material and passivating the very smooth edge with a thin coat of silicon oxide. We report a comparison of I-V measurements and charge collection and noise measurements on two identical sensors, one with and one without slim edge treatment. The current voltage measurements of the entire sensor and individual strips indicate that the large current increase due to the treatment is confined to the guard ring, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The IV curves were collected by using a Keithley 237 high voltage source measurement unit. We also collected charge collection data for these sensors; these measurements are presented in different publications [8,9]. A short summary is given below, section 2.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IV curves were collected by using a Keithley 237 high voltage source measurement unit. We also collected charge collection data for these sensors; these measurements are presented in different publications [8,9]. A short summary is given below, section 2.5.…”
Section: Resultsmentioning
confidence: 99%
“…We performed charge collections measurements for n-and p-type sensors. R. Mori et al [8] looked into the pulse height distribution of the signals from a beta source with the ALiBaVa system [18]. The sensors were n-type test devices from GLAST/Fermi production [10].…”
Section: Charge Collection Measurementsmentioning
confidence: 99%
“…The detectors are first laser scribed and cleaved then the edges are passivated using SiO 2 /Si 3 N 4 for n-type or Al 2 O 3 for p-type silicon. Good performance of the 'slim edge' sensors (IV curve and charge collection efficiency) has been reported [31]. The range detector will be assembled using 4 mm thick Polystyrene fast scintillator blocks ( Fig.…”
Section: Future Developmentsmentioning
confidence: 98%
“…Individual strip currents before and after cutting are essentially unchanged. In addition, we have found that the charge collection on the strips next to the slim edge is unchanged when compared to before cleaving [12]. Up to now, about 50 test structures with edge length up to 10 cm have been treated successfully with distances down to 14 μm between active area and edge.…”
Section: Tracker Design and Randdmentioning
confidence: 99%